New era towards advancing in girls' and women's health and rights? - Belizan, Jose (2017)
Whenever there are leadership changes in the global health sphere, there are always expectations, hopes, and optimism. 2017 ushers in a new era of global leadership at the World Health Organization (WHO) and the UN. All of us involved in making reproductive health more equitable, particularly for the most ulnerable, would like to see profound and rapid changes. During the campaign for the Director General (DG) position at WHO, the candidates responded to a series of questions from the organization,Women Deliver, (http://womendeliver.org/2017/close-personal-three-final-director-general-candidates/).